Characterization of nonpathological intrascleral cartilage in the domestic sheep (Ovis aries)1 - Teodoro, Tamires G.W.; Campos, Maria Eduarda S.T.; Silva, Laice A.; Watanabe, Tatiane T.N.; Alves, Carlos Eduardo F.; Laufer-Amorim, Renée [UNESP]; Wouters, Flademir; Wouters, Angelica T.B. (FapUNIFESP (SciELO), 2023)
Teodoro T.G.W., Campos M.E.S.T., Silva L.A., Watanabe T.T.N., Alves C.E.F., Laufer-Amorim R., Wouters F. & Wouters A.T.B. 2023. Characterization of nonpathological intrascleral cartilage in the domestic sheep (Ovis aries). Pesquisa Veterinária Brasileira 43:e07142, 2023. Setor de Patologia Veterinária, Departamento de Medicina Veterinária, Faculdade de Zootecnia e Medicina Veterinária, Universidade Federal de Lavras, Campus Universitário, Cx. Postal 3037, Lavras, MG 37200-900, Brazil. E-mail: angelica.wouters@ufla.br Birds, cartilaginous and teleost fish, reptiles, and some amphibians have intrascleral cartilage and/or bone; however, these are rarely reported in therian mammals. This study aimed to investigate and characterize a nonpathological formation of cartilage in the posterior sclera of sheep macroscopically, histologically, and by immunohistochemical exam (IHC). Ninety eyes from 45 domestic sheep were collected, underwent gross examination, fixed in formalin, and embedded in paraffin for the microscopical assessment. Sections with histological shreds of cartilage were selected to perform IHC to confirm the presence of cartilage. Intrascleral cartilage was detected in 60 eyeballs (66.66%) from 37 sheep (82.22%). A slight whitish thickening was grossly seen in the posterior sclera. The histologic exam revealed a few scattered, isolated chondrocytes to larger aggregates of cartilaginous islands in the posterior sclera. Eighteen (30%) of 60 eyeballs revealed marked anti-collagen type II immunolabeling. The development of cartilaginous structures in the eyes is considered rare in mammalian animals. The high occurrence of intrascleral cartilage in the examined sheep eyes suggests that this finding corresponds to an anatomical component of sheep sclera, despite the age, breed, or body condition.
Keywords: ocular anatomy; ocular cartilage; Ophthalmology; Ovis aries; sheep